Climate Change: Gets Mo Na Ba? Mobilizing Science for Climate Change, Agriculture & Food Security: Engaging the Philippine Regional Media Seminar-Workshop Report - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This report highlights the results of the conduct of the first of a series of four seminar – workshops on climate change, agriculture and food security for the Philippine regional media co-sponsored by the CCAFS Regional Program for Southeast Asia (CCAFS – SEA) in collaboration with the MVP Group of Companies (i.e., Metro Pacific Investments Corp., Philex Mining Corp. and Smart Communications), Philippine Agriculture Journalists, Inc. (PAJ) and the Department of Agriculture (DA). Held on 30 July-01 August 2015 in Legazpi, Albay, this was pursued with the Philippine Federation of Rural Broadcasters (PFRB), Philippine Network of Environmental Journalists (PNEJ) and Philippine Science Journalists, Inc. (PSciJourn) as partners. This initiative was an offshoot of the first inter-Center media seminar-workshop conducted by CCAFS-SEA in the Philippines on 14 –15 August 2014 in Los Baños, Laguna, Philippines.